Not Just a Slice: Animal Crossing and a Life Ongoing - Straznickas, Gracie Lu (Loading, 2020)
This paper defines and examines a genre of videogames I call slice of life and reflects upon the use and appeal of the genre for different audiences. I develop an account of the slice of life genre by defining three critical traits: the mundane activities comprising most of the game time, the normativity of social interactions within the world, and the ongoingness of the game world in the absence of the player. Utilizing a journal and experience-based methodology, I present my own experience with chronic pain and pain management to assess how Animal Crossing: New Leaf, a game that falls into this slice of life category, was useful to me as a disabled player. My analysis not only reveals a connection between my experience in Animal Crossing: New Leaf and pain management, but also offers insight into how the slice of life genre involves different metagames for different audiences. Future work may address more case studies in further development of the slice of life genre as well as how it impacts different audiences.